2020
DOI: 10.1177/1526602820931559
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Drug-Coated Balloon Angioplasty for the Treatment of Chronic Limb-Threatening Ischemia: A Systematic Review and Meta-Analysis

Abstract: Purpose: To investigate the safety and efficacy of drug-coated balloons (DCB) for the treatment of femoropopliteal or infrapopliteal lesions in patients with chronic limb-threatening ischemia (CLTI). Materials and Methods: A systematic literature search was conducted in PubMed, Scopus, and Cochrane Central up to January 2020 to identify randomized trials and observational studies presenting data on the effectiveness and safety of DCBs in the treatment of femoropopliteal or infrapopliteal lesions. A meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
7
0
3
Order By: Relevance
“…The mechanism of balloon angioplasty consists of adventitial stretching, medial necrosis, and dissection or plaque fracture. 17 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of balloon angioplasty consists of adventitial stretching, medial necrosis, and dissection or plaque fracture. 17 18…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of balloon angioplasty consists of adventitial stretching, medial necrosis, and dissection or plaque fracture. 17,18 In this prospective observational study, we have evaluated the safety and efficacy in terms of 6 monthly primary patency rates of DEB in BTK arterial disease presented with CLI. The results showed that DEB achieved promising clinical outcomes with successful performance in IP arteries in the short-term follow-up with a substantial primary patency rate (76%) that is much better as compared to standard percutaneous transluminal angioplasty (38%).…”
Section: Discussionmentioning
confidence: 99%
“…nach PCB weniger erneute Revaskularisierungen nötig als nach POBA. Frühere randomisierte Studien konnten dagegen keinen Vorteil von PCB hinsichtlich primärer Offenheit, erneuter Revaskularisierung, Amputationsrate und Mortalität zeigen [4]. Darüber hinaus zeigte eine Metaanalyse von acht randomisierten Studien, dass ein Jahr nach Behandlung mit PCB weniger Patienten ohne Amputation überlebt hatten als nach POBA [5].…”
Section: Diskussionunclassified
“…3 In the BEST-CLI, the endovascular techniques applied to CLTI patients included the use of atherectomy (15%), drug-coated balloons (25%) and drugeluting stents (22%). 1 With wider application of advanced endovascular techniques, [4][5][6][7] the outcomes of patients offered endovascular treatment are expected to improve. Thus, the BEST-CLI results may become outdated.…”
mentioning
confidence: 99%